The Effect of Price and Brand Image on Interest in Buying Rabbani Hijab (Case Study of Students of Universitas Islam Darul 'Ulum Lamongan) - Dilla Riyanika; Syuhada' Syuhada'; Ahmad Munir Hamid (AJER: Advanced Journal of Education and Religion, 2024)
This study aims: 1) To determine the effect of price on purchase intention of Rabbani hijab. 2) To determine the effect of brand image on the purchase intention of Rabbani hijab. 3) To determine the effect of price and brand image on the intention to buy Rabbani hijab. This research uses quantitative methods. The research population was 113 female students at Darul Ulum Lamongan Islamic University. The Slovin formula determined the research sample, so 89 respondents were obtained. The data collection technique used a questionnaire with 15 statement items measured using a Likert scale of 1 to 5 and tested for validity and reliability. The data analysis technique used is multiple linear regression analysis to answer the hypothesis. The results showed that the partial test of the price variable had a significant effect on buying interest with 2.312 > ttable 1.987 and a substantial value of 0.023 <0.05. From the brand image variable, it has a significant effect on purchase intention, showing 4,564 > 1,987 with a substantial value of 0.000 <0.05. Then, the simultaneous test of price and brand image variables has a significant effect on the purchase intention of Rabbani hijab, showing 22.119 > 3.10 with an essential value of 0.000 <0.05. The R Square result of 34.0% shows the influence of Islamic business ethics and creativity on business people's profits. Meanwhile, 66.0% is influenced by other variables outside the research.